2019
DOI: 10.1111/bor.12368
|View full text |Cite
|
Sign up to set email alerts
|

Recursive anisotropy: a spatial taphonomic study of the Early Pleistocene vertebrate assemblage of Tsiotra Vryssi, Mygdonia Basin, Greece

Abstract: By applying advanced spatial statistical methods, spatial taphonomy complements the traditional taphonomic approach and enhances our understanding of biostratinomic and diagenetic processes. In this study, we elaborate on a specific aspect – spatial anisotropy – of taphonomic processes. We aim to unravel the taphonomic history of the Early Pleistocene vertebrate assemblage of Tsiotra Vryssi (Mygdonia Basin, Greece). Circular statistics are used for the fabric analysis of elongated elements; geostatistics (dire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Specimens that could not be identified taxonomically but belong to the aforementioned size groups are also included in some of the analyses (n = 77). Concerning the collection protocol of fossils during the excavation, collected were all diagnostic (to skeletal element) bones and teeth, as well as carnivore modified bones, regardless of their preserved size; not collected, yet recorded (location, dimensions) with the total station were non-diagnostic bone fragments with length of ≥50 mm, while non-diagnostic and non-carnivore modified fragments ≤50 mm were not recorded (Giusti et al 2019). Although this sampling protocol introduces few limitations in some of the analyses included in this study, we believe that these are only minor and that the studied sample is sufficient for a safe interpretation of the site.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specimens that could not be identified taxonomically but belong to the aforementioned size groups are also included in some of the analyses (n = 77). Concerning the collection protocol of fossils during the excavation, collected were all diagnostic (to skeletal element) bones and teeth, as well as carnivore modified bones, regardless of their preserved size; not collected, yet recorded (location, dimensions) with the total station were non-diagnostic bone fragments with length of ≥50 mm, while non-diagnostic and non-carnivore modified fragments ≤50 mm were not recorded (Giusti et al 2019). Although this sampling protocol introduces few limitations in some of the analyses included in this study, we believe that these are only minor and that the studied sample is sufficient for a safe interpretation of the site.…”
Section: Methodsmentioning
confidence: 99%
“…Two main depositional units have been identified at TSR, Geo 1 and Geo 2, of which the ~1 m thick fossiliferous Geo 2a consists of pale brown-to dark yellowish brown very fine sandy silts, locally intercalated by cm-thick lenses of medium-coarse grained sands (Giusti et al 2019). Previous spatial taphonomic analyses of the vertebrate assemblage, in agreement with sedimentological and micromorphological observations, suggested that multiple dispersion events occurred in the formation of the deposit: the recurrent spatial rearrangements of a lag, (peri)autochthonous assemblage being consistent with the cyclical lateral switching of a braided fluvial system (Giusti et al 2019). Cosmogenic radionuclides, magnetostratigraphy and biochronological data indicate an age between 1.78 and ~1.5 Ma (late Villafranchian, Lower Pleistocene) for the site (Konidaris et al , 2022.…”
Section: Geological Palaeontological and Chronological Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, fabric analysis on natural clasts within a debris flow reveals that the long axes of clasts are often oriented parallel to the slope direction (Bertran et al 1997;Lenoble and Bertran 2004), to the extent that the clast in these deposits show weak or strong imbrication, as is the case in grain flows (Bertran and Texier 1999). Therefore, by recording the orientation (trend and bearing) of elongated artefacts and natural clasts during excavation, researchers can use fabric analysis to reconstruct potential modes of deposition (Benito-Calvo et al 2009;Sánchez-Romero et al 2016;McPherron 2018;Giusti et al 2019;Li et al 2021) and also investigate the impacts that previous substrate morphologies have on the clast orientation (Li et al 2021). Despite the increasing regularity with which fabric analysis has been employed for the reconstruction of site formation processes, little work to date has focused on the analysis of fabrics internal to combustion features.…”
Section: Introductionmentioning
confidence: 99%